EVALUASI TATA KELOLA TERMINAL TIPE C TUAH TUALANG DI KABUPATEN SIAK - Puspita, Ike; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Siak Regency is one of  the Districts that has excellent tourist destinations, which in the presence of superior tourist destinations, transportations facilities and infrastructure are needed as tourism support in Siak Regency. One of the problems of transportation facilities and infrastructure is the management of Tuah Tualang Type C Terminalsin Siak Regency, this is because there are still many shadow terminals and ticket agents around the Tualang Sub-District road and the public transport route network has not been arranged. The purpose of this study was to evaluate terminal management and look at the evaluation factors for the management of  Tuah Tualang Type C Terminal in Regency. The theoretical concept used is the theory of evaluation by Dunn in (Nugroho, 2017), namely : effectiveness, efficiency, sufficiency, equity, responsiveness, and determination. This study uses qualitative methods with a case study approach, and uses purposive sampling technique, with data collection thecniques including : observation, interviews, and documentation. The results of the evaluation of the management of the type C terminal of  Tuah Tualang in Siak Regency have not run optimally and have not been realized properly. it is better to improve the status of the terminal to type A and to arrange a system for the public transport route network at the Tuah Tualang terminal in Siak Regency. Keywords : Evaluation, Governance, Terminal